Effect of Ni-Co Ratio on ZSM-5 Catalyst Performance in Palm Oil Hydrocracking for Biofuel Production - Istadi, I.; Riyanto, Teguh; Permatasari, Astrid Eka; Dinara, Daniella Cipta (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2025)
Biofuel derived from vegetable oil can be utilized as a vehicle fuel with various advantages, such as renewability, environmental friendliness, and sustainable availability. One of the methods for converting vegetable oil into biofuel is hydrocracking. This study investigates Ni-Co/ZSM-5 catalyst with Ni-Co metal ratios of 1:0.5, 1:1, and 1:1.5 to examine their effects on the catalyst characteristics and performance in the hydrocracking process of palm oil into biofuel. The catalyst synthesis was carried out using the co-impregnation method with ultrasound assistance, followed by characterization using XRD and XRF. The hydrocracking process was conducted at a temperature of 450℃ and a WHSV of 0.1 min-1, while the gas product was analyzed using GC and liquid product was distilled. XRF results showed that the actual Ni-Co ratio did not significantly differ from the designed ratio. XRD analysis indicated crystal agglomeration at a 1:1.5 ratio due to competition between Ni and Co metal particles diffusing into the zeolite pores, as well as the presence of dislocations and crystal defects. Differences in catalyst characteristics resulted in variations in yield, selectivity, and gas distribution in the hydrocracking process. The catalyst with a Ni-Co ratio of 1:1.5 exhibited the highest liquid product yield and biogasoline selectivity but also produced a higher concentration of CO, CO2, and C2 gases. It is associated with the breakdown of triglycerides into fatty acids, which subsequently fragment into shorter-chain biofuel components.